Between beliefs, traditional practices, and modern care: Parental perceptions in the management of paediatric chronic diseases - DIWOTO DOWO, Jean-Paul; Amuli , Jiwe Jean-Pierre; Mabakutuvangilanga, Ntela Simon-Decap; Mukandu, Basua Babintu Leyka (Orapuh Journal, 2025)
IntroductionIn the Democratic Republic of Congo (DRC), perceptions of paediatric chronic illnesses remain strongly shaped by cultural and spiritual beliefs. These beliefs influence care-seeking behaviours and treatment adherence. However, few studies have explored the lived perceptions of families in Kinshasa.Purpose To explore the beliefs, traditional practices, and expectations of families regarding the hospital management of paediatric chronic illnesses.Methods An exploratory qualitative study was conducted with 10 parents or guardians of children hospitalised for chronic illness at the University Hospital Centre Renaissance in Kinshasa. Semi-structured interviews were conducted in French or Lingala to collect their experiences. Data were analysed using Braun and Clarke’s six-phase inductive thematic approach, validated through double coding, and interpreted within the framework of Leininger’s transcultural theory.ResultsThree main themes emerged. Most parents (7 out of 10) attributed their child’s chronic illness to supernatural causes such as curses, witchcraft, or divine testing. More than half (6 out of 10) first used traditional or religious remedies before seeking hospital care, with family and community support playing a central role. Although some participants acknowledged the effectiveness of medical treatment, several reported financial constraints, insufficient attentive listening, and weak communication from healthcare providers. A majority of families (8 out of 10) expressed a strong need for respect for their beliefs, involvement in decision-making, and recognition of their knowledge and traditions.Conclusions Parental perceptions directly influence treatment pathways. Integrating families’ beliefs and expectations into the care relationship is essential to strengthen therapeutic adherence. The study highlights the need for a culturally sensitive approach, including community mediation, intercultural communication training for healthcare professionals, and family-centred therapeutic education.